PEMBIASAAN BERDO’A SEBELUM BELAJAR DALAM MENINGKATKAN KECERDASAN SIKAP SPIRITUAL (Studi Deskripsi di Madrasah Aliyah Cilenga dan Madrasah Al-Hamidiyah Cipancur Kabupaten Tasikmalaya) - Abdul Muiz; Ahmad Sukandar; Husen Saepul Insan (JURNAL ILMIAH EDUKATIF, 2022)
Research studi conducted by researchers at several Madrasah Aliyah in Tasikmalaya Regency, Many students forget to read the prayer before studying even though the benefits are very much. This is because the planning, implementation, assessment, supporting and inhibiting factors are not yet optimal. The purpose of this study was to determine the planning, implementation, assessment of the habit of praying, supporting and inhibiting factors and solutions for habituation of praying before learning in increasing the intelligence of students' spiritual attitudes. This research method uses a qualitative approach with case study methods and data collection techniques through observation, interviews and documentation studies. While the data sources are the principal, teachers and students. The results showed; First, in the planning aspect, habituation starts from setting goals, determining materials, programs, activities and assessment tools. Second, the implementation is carried out individually, in the classroom, the teacher guides, gives examples, explains the virtues, benefits and procedures for good prayer. Third, the assessment is carried out in the middle of the semester, the end of the semester or the end of the school year. Assessment includes planning, implementation, and results of habituation. Fourth, the supporting and inhibiting factors are the limited facilities and the guiding teacher. In general, prayer habituation activities have been running smoothly, but spiritual intelligence has not taken root in all students because there are still inhibiting factors, including students and teachers who come late, and are not yet optimal. discipline and understanding habituation to pray.